Quadratic Equations#1

Algebra Level 3

If equation x 2 2 a x c = 0 x^2 - 2ax - c = 0 have exactly one root common with each of equation x 2 4 x + 1 = 0 x^2 - 4x + 1 = 0 and x 2 + 8 x + 13 = 0 x^2 + 8x + 13 = 0 . Which will always be correct:

  1. a a is a rational number
  2. a a is an irrational number
  3. c c is an irrational number
  4. c c is a rational number


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Jan 21, 2018

Let r 1 , r 2 r_1, r_2 be the roots of x 2 4 x + 1 = 0 x^2 - 4x +1 = 0 and x 2 + 8 x + 13 = 0 x^2 + 8x + 13 = 0 respectively, which compute to:

r 1 = 2 ± 3 , r 2 = 4 ± 3 r_1 = 2 \pm \sqrt{3}, r_2 = -4 \pm \sqrt{3}

If the quadratic equation x 2 2 a x c = 0 x^2 - 2ax - c = 0 contains one root of each, then we have:

x 2 2 a x c = ( x r 1 ) ( x r 2 ) = 0 x 2 ( r 1 + r 2 ) x + r 1 r 2 = 0 x^2 - 2ax - c = (x - r_1)(x - r_2) = 0 \Rightarrow x^2 - (r_1 + r_2)x + r_1 r_2 = 0 ; or 2 a = r 1 + r 2 , c = r 1 r 2 \boxed{2a = r_1 + r_2, c = -r_1 r_2} .

Checking each possible root combination for 2 a , c 2a, c yields:

2 a = ( 2 + 3 ) + ( 4 + 3 ) a = 1 + 3 2a = (2+\sqrt{3}) + (-4 + \sqrt{3}) \Rightarrow a = -1 + \sqrt{3} (IRRATIONAL);

2 a = ( 2 + 3 ) + ( 4 3 ) a = 1 2a = (2+\sqrt{3}) + (-4 - \sqrt{3}) \Rightarrow a = -1 (RATIONAL);

2 a = ( 2 3 ) + ( 4 + 3 ) a = 1 2a = (2-\sqrt{3}) + (-4 + \sqrt{3}) \Rightarrow a = -1 (RATIONAL);

2 a = ( 2 3 ) + ( 4 3 ) a = 1 3 2a = (2-\sqrt{3}) + (-4 - \sqrt{3}) \Rightarrow a = -1 - \sqrt{3} (IRRATIONAL);

c = ( 2 + 3 ) ( 4 + 3 ) c = 5 + 2 3 c = -(2+\sqrt{3})(-4+\sqrt{3}) \Rightarrow c = 5 + 2\sqrt{3} (IRRATIONAL);

c = ( 2 + 3 ) ( 4 3 ) c = 11 + 6 3 c = -(2+\sqrt{3})(-4-\sqrt{3}) \Rightarrow c = 11 + 6\sqrt{3} (IRRATIONAL);

c = ( 2 3 ) ( 4 + 3 ) c = 11 6 3 c = -(2-\sqrt{3})(-4+\sqrt{3}) \Rightarrow c = 11 - 6\sqrt{3} (IRRATIONAL);

c = ( 2 3 ) ( 4 3 ) c = 5 2 3 c = -(2-\sqrt{3})(-4-\sqrt{3}) \Rightarrow c = 5 - 2\sqrt{3} (IRRATIONAL).

After this exhaustive exercise, only Choice (3) is the correct one.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...